2015
DOI: 10.1016/j.microc.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of marine aerosol in the formation of (double) sulfate/nitrate salts in plasters

Abstract: During decades the use of gypsum in different buildings has been very common, especially in the Atlantic lands of Europe. Decay compounds like salt crystallizations are ones of the principal deterioration factors of such historical buildings. In this study, gypsum-based plasters from different inner rooms of the Igueldo Lighthouse (San Sebastian, Spain), a building dated back to 1860 that has been subjected to several repairs within these years, were investigated in order to ascertain the main mineral phases p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…The sensitivity of Raman spectroscopy for low crystallized phases and the microscopic resolution fulfils the requirements for protective ability index's calculations for complex and heterogeneous corroded layers. Madariaga's group demonstrated at the laboratory and with appropriate software that the portable spectrometer is very useful to select the most representative spots for sampling and comprehensive study …”
Section: Study Of Refractory (Inorganic) Materials—examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of Raman spectroscopy for low crystallized phases and the microscopic resolution fulfils the requirements for protective ability index's calculations for complex and heterogeneous corroded layers. Madariaga's group demonstrated at the laboratory and with appropriate software that the portable spectrometer is very useful to select the most representative spots for sampling and comprehensive study …”
Section: Study Of Refractory (Inorganic) Materials—examplesmentioning
confidence: 99%
“…Stone and plaster corrosion are also important questions where Raman studies can help understand mechanisms and solve problems. Using measurements being made at the laboratory on sampled fragments, Morillas et al showed that a combination of X‐ray fluorescence and Raman on site measurements is sufficient to draw conclusions. A rather similar approach can be taken for bronze artefacts and for glass (but at smaller scale).…”
Section: Study Of Refractory (Inorganic) Materials—examplesmentioning
confidence: 99%
“…The results presented in this work evidence the necessity of combining Raman results with the ones extracted with additional techniques in order to contrast and complement the Raman evidences . Sometimes, the Raman bands obtained are very weak; thus, the assignations performed using these techniques can be uncertain.…”
Section: Discussionmentioning
confidence: 79%
“…XRD analyses were performed using a diffractometer (PANalytical Xpert PRO, Almelo, The Netherlands) provided with a Cu tube ( λ Cu k α average = 1.5418 Å, λ Cu k α 1 = 1.5460 Å and λ Cu k α 2 = 1.54439 Å), a vertical goniometer (Bragg‐Brentano geometry), programmable divergence slit, automatic sample exchanger, secondary graphite monochromator and PixCel detector. Additional information of the instrument and measurement conditions can be revised elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Evaporation will cause the saturation of a solution, and this relies on the temperature, the relative humidity (%RH) of the environment, and the chemical composition of the solution . Variations in %RH and temperature around or inside buildings play an important role in the crystallization or dissolution of different salts …”
Section: Introductionmentioning
confidence: 99%